ANALISIS KEMAMPUAN BERPIKIR KRITIS PADA PELAJARAN IPAS SISWA KELAS V DI MIN 25 ACEH UTARA - Syahbandi; Aisyah Ma’awiyah; Zainal Abidin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Critical thinking is one of the essential competencies that should be developed in twenty-first-century learning, particularly in Natural and Social Science (IPAS) education. However, elementary school students' critical thinking skills still require significant improvement to meet the demands of the Merdeka Curriculum. This study aimed to analyze the critical thinking skills of fifth-grade students in the IPAS subject on the topic What Is a Food Chain? at MIN 25 Aceh Utara and to identify the factors influencing these skills. This research employed a qualitative approach using a field research design. The research subjects consisted of 32 fifth-grade students, while the informants included two IPAS teachers and six students selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation. Data validity was ensured through source and technique triangulation, while data analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings revealed that students' critical thinking skills were moderately developed but had not reached an optimal level across all of Ennis's critical thinking indicators. Students experienced difficulties in analyzing relationships among living organisms, providing logical reasoning, developing comprehensive explanations, and solving problems systematically. The findings also indicated that critical thinking skills were influenced by several factors, including teaching methods, instructional media, learning motivation, prior knowledge, learning environment, and students' self-confidence. These findings highlight the importance of creating meaningful learning experiences that actively engage students in inquiry, discussion, and problem-solving activities. Therefore, student-centered learning strategies supported by appropriate instructional media and interactive classroom practices should be implemented to improve students' critical thinking skills in IPAS learning and enhance the overall quality of elementary education.